Heat Unit–Based Prediction of Harvest Age in Rice under Different Planting Spacings and Genotypes - Yohana Kathryn Siahaan; Dulbari Dulbari; Juwita Suri Maharani; Moh Haris Imron S Jaya (The University of Lampung, 2026)
Heat unit (HU) is widely used to describe crop thermal requirements; however, its application for determining rice harvest age across different planting spacings and genotypes remains limited. This study aimed to evaluate the effects of plant spacing and genotype on HU accumulation and to assess the usefulness of HU as a predictor of harvest age and yield-related traits in rice. The experiment was conducted in a greenhouse using a factorial randomized complete block design with three planting spacings (Jarwo 2:1, Tegel 25 cm × 25 cm, and transplanter-based spacing 35 cm × 15 cm) and four rice genotypes (PTP 01, Inpari 24, Jeliteng, and Pandan Wangi). Results showed that HU accumulation during the vegetative phase was uniform across all treatments, reaching approximately 776 °C⸳day, indicating a common thermal threshold for early growth. In contrast, significant differences emerged during the generative phase and at harvest. Plant spacing significantly affected HU accumulation and harvest timing, whereas genotype did not alter total HU requirement but strongly influenced yield expression. The Jarwo 2:1 system required the lowest total HU to reach physiological maturity ( 1134 °C⸳day), followed by Tegel 25×25 cm ( 1146 °C⸳day) and transplanter spacing ( 1159 °C⸳day). Inpari 24 consistently exhibited superior plant height, grain filling, and grain weight per panicle, indicating higher efficiency in converting accumulated HU into yield. Heat unit–based thresholds provide a reliable tool for predicting rice harvest age and optimizing genotype–spacing combinations.